Focused Principal Component Analysis: a graphical method for exploring dietary patterns Análise de Componente Principal Focada: um método gráfico para explorar padrões alimentares - Raquel Canuto; Suzi Camey; Denise P. Gigante; Ana M. B. Menezes; Maria Teresa Anselmo Olinto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of the present study was to introduce Focused Principal Component Analysis (FPCA) as a novel exploratory method for providing insight into dietary patterns that emerge based on a given characteristic of the sample. To demonstrate the use of FPCA, we used a database of 1,968 adults. Food intake was obtained using a food frequency questionnaire covering 26 food items. The focus variables used for analysis were age, income, and schooling. All analyses were carried out using R software. The graphs generated show evidence of socioeconomic inequities in dietary patterns. Intake of whole-wheat foods, fruit, and vegetables was positively correlated with income and schooling, whereas for refined cereals, animal fats (lard), and white bread this correlation was negative. Age was inversely associated with intake of fast-food and processed foods and directly associated with a pattern that included fruit, green salads, and other vegetables. In an easy and direct fashion, FPCA allowed us to visualize dietary patterns based on a given focus variable. O presente estudo teve objetivo de apresentar a Análise de Componentes Principais Focada (ACPF) como um método exploratório para investigar padrões alimentares a partir de características da amostra. Para exemplificar utilizou-se as variáveis idade, renda e escolaridade de um banco de dados de 1.968 adultos. O consumo alimentar foi obtido através questionário de frequência alimentar (QFA) com 26 itens alimentares. As análises foram realizadas no programa R. Os gráficos gerados evidenciaram iniquidades socioeconômicas na conformação dos padrões alimentares. Alimentos integrais, frutas e verduras foram diretamente correlacionados com renda e escolaridade, e cereais refinados, gordura animal e pão branco tiveram associação inversa. A idade mostrou-se como associada inversamente a alimentos fast-food e industrializados e, diretamente, a um padrão "saudável" que inclui frutas, salada verde e outros vegetais. De maneira fácil e direta, a ACPF permitiu a visualização de correlações entre alimentos a partir de variáveis escolhidas como foco.